1991
DOI: 10.1103/physrevb.44.9853
|View full text |Cite
|
Sign up to set email alerts
|

Tin tetrabromide at high pressures: Reversible crystalline-to-amorphous and electronic transitions

Abstract: Several phase transitions have been observed in SnBr4 up to 23 GPa. Measurements of the Raman spectra show that additional modes are observed in the lattice region at about 4 GPa, suggesting that the symmetry of the unit cell is changing. All lattice modes disappear and the internal vibrational modes lose their splitting in the 13 -15-GPa region, indicating that a crystal-to-amorphous transition occurs in this pressure range. Upon release of pressure, the amorphous phase is stable to about 1 GPa. A crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…This is consistent with the already observed amorphization of all examined members of this family at pressures above 8 to 10 GPa. 2,[21][22][23][24] There are distinct analogies between the ionic size ratio systematics identified here for crystalline to noncrystalline transitions and those found to dictate crystal-crystal phase transitions in a variety of simpler system such as alkali halides. For example in sodium halides, NaF and NaCl undergo the well documented B1-B2 transition at pressure.…”
Section: Discussionmentioning
confidence: 85%
“…This is consistent with the already observed amorphization of all examined members of this family at pressures above 8 to 10 GPa. 2,[21][22][23][24] There are distinct analogies between the ionic size ratio systematics identified here for crystalline to noncrystalline transitions and those found to dictate crystal-crystal phase transitions in a variety of simpler system such as alkali halides. For example in sodium halides, NaF and NaCl undergo the well documented B1-B2 transition at pressure.…”
Section: Discussionmentioning
confidence: 85%
“…LiInGe is an example for an reversible pressure induced amorphization of a compound with zincblende-like partial structure. L r X Structural memory behaviour has also been reported for Alp04 [23], [24] and several other compounds, for example molecular solids like SnBr4 1251, [26], SnI4 [27] to [29] and GeI4 [30]. This effect suggests that the atomic disorder produced by pressure derives from a relative small perturbation of the crystalline structure.…”
Section: Resultsmentioning
confidence: 85%
“…Previous Raman and reflectiwty studies by Williams and Lee [9 ] have shown that to the highest pressure measured (25 GPa) there is no gap closure and SnBr4 remains a bonajde insulator. Fig.…”
Section: Snbr4mentioning
confidence: 73%